Penggunaan Metode Bilqolam dalam Meningkatkan Kualitas Baca Tulis Al Quran di Era Digitalisasi Siswa Kelas VI MI Syaichona Cholil Teluk Pandan Tahun Pelajaran 2023/2024 - Umar, Umar; Minarsih, Minarsih (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
In facing the challenges of the digital era, it is crucial to innovate effective learning methods to enhance the quality of Quranic literacy. This research aims to explore the use of the Bilqolam method, focusing on improving the Quranic reading and writing skills of sixth-grade students. The research employs a qualitative method, with data collection techniques including observation, interviews, and documentation. This method is applied to enhance the quality of Quranic reading and writing. The data indicate that the Bilqolam method has a significantly positive impact on learning, especially in deepening students' understanding of Quranic readings. The learning structure, consisting of opening, core, and closing segments, has proven effective in improving Quranic literacy scores. The research findings also reveal differences in the improvement of each student's Quranic reading and writing scores, with significant advancements in tahsin abilities, mastery of tajweed, memorization of short surahs, and overall Quranic literacy skills. In conclusion, the Bilqolam method is effective in enhancing the Quranic literacy quality of sixth-grade students through a qualitative approach, as evidenced by significant improvements in tajweed understanding, tahsin, surah memorization, and overall Quranic reading and writing abilities.